"Mother of the Oceans": Maritime Governance as a Template for a New Global Order in the International Thought of Elisabeth Mann Borgese (1918–2002). Issue 1 (29th March 2023) - Ashworth, Lucian M
Abstract: This article explores the international thought of Elisabeth Mann Borgese (1918–2002), a major figure in the third United Nations Conference on the Law of the Sea negotiations and (later in her life) a professor at Dalhousie University. Borgese's analysis of the nature of the Ocean led her to see the emerging system of maritime governance as a template for wider global governance. The fluidity of the Ocean, she argued, blurred terrestrial certainties, while the fundamental interdependence of its ecosystems means that its governance offers a new paradigm that can inform terrestrial governance. The Ocean has always been important, she argued, but that importance is now increasing. Thus, in Borgese's work, the Ocean emerges as more than a passive victim of human exploitation, and becomes a positive influence on humanity's future. Taking her work seriously helps international relations (IR) confront its own failure to engage with global physical realities and would be another step toward rewriting an IR for the Anthropocene.